Analisis Strategi Bersaing Pada Bisnis Kuliner (Studi Kasus Pizza Apa Ya) - Muthmainnah, Hafsah; Triyanto, Abdi (Prodi Manajemen Bisnis Syariah, 2024)
This study aims to find out and describe how the competitive strategy carried out by Pizza Apa Ya in the face of competition. This research is a qualitative descriptive study using Porter's generic analysis. The data used are primary data obtained through an interview process with the President Commissioner of SL Corp Indonesia and secondary data sourced from literature studies in the form of books and journals. The data obtained is then processed using SWOT analysis to be able to find out what are the factors of strengths, weaknesses, threats, and opportunities that Pizza Apa Ya has. The results of the research on the generic strategy of Pizza Apa Ya show that the company implements a generic competitive strategy in the form of cost leadership and differentiation.